ANTESEDEN DARI CARE COORDINATED PATHWAYS DAN DAMPAKNYA PADA PATIENT CENTRICITY - Sari, Ni Komang Yeni Dhana (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
Patient centricity is one of the qualities in health services. In order to improve patient centricity, service coordination through care coordinated pathways is crucial to provide the best clinical experience for patients. However, there has been no research in Indonesia regarding care coordinated pathways and their impact on patient centricity. This study was conducted to determine antecedents of care coordinated pathways with elements of cross-functional teamwork, mutual communication, goal alignment, and shared accountability, and also their effect on patient centricity. This research model was tested on a population of health workers at Hermina Daan Mogot Hospital, Jakarta. The data collection was carried out by purposive sampling with a total of 168 samples. Data were analyzed using the PLS-SEM method. The results of this study indicate that cross-functional teamwork, mutual communication, goal alignment, and shared accountability have a significant effect on care coordinated pathways. In addition, care coordinated pathways have a significant effect on patient centricity. The results of this study provide useful implications for managerial applications in health care centers.